1994
DOI: 10.2307/3283403
|View full text |Cite
|
Sign up to set email alerts
|

Lead Accumulation in Pomphorhynchus laevis and Its Host

Abstract: Adults of Pomphorhynchus laevis were collected from the intestines of 10 chubs (Leuciscus cephalus) from the river Ruhr near Bochum, Germany. The acanthocephalans and various tissues of the fish (muscle, liver, and intestine) were analyzed for lead with electrothermal atomic absorption spectrometry. The mean lead level in the parasite was 54 micrograms/g wet weight, which was 284 times more than in the host intestine, 771 times more than in host liver, and 2,700 times more than in host muscle. Thus, P. laevis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 16 publications
3
25
1
Order By: Relevance
“…These are lower than corresponding values of 2700, 770 and 280 obtained for P. laevis in chub from the industrially polluted River Ruhr in Germany (Sures et al 1994) despite the environmental lead concentration at the German site being half that in this experimental study. Sures et al (1994) recorded a mean lead concentration in the worms of 54 lg g A1 which was 15 times higher than the levels in this experiment. Therefore, metal concentrations in the parasites are unlikely to have peaked after only 3 weeks in 0.01 mg l A1 Pb 2+ and may have continued increasing with a prolonged exposure.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…These are lower than corresponding values of 2700, 770 and 280 obtained for P. laevis in chub from the industrially polluted River Ruhr in Germany (Sures et al 1994) despite the environmental lead concentration at the German site being half that in this experimental study. Sures et al (1994) recorded a mean lead concentration in the worms of 54 lg g A1 which was 15 times higher than the levels in this experiment. Therefore, metal concentrations in the parasites are unlikely to have peaked after only 3 weeks in 0.01 mg l A1 Pb 2+ and may have continued increasing with a prolonged exposure.…”
Section: Discussioncontrasting
confidence: 79%
“…A recent series of studies by Sures and co-workers revealed a remarkable capacity of adult acanthocephalans in the intestines of ®sh to bioconcentrate heavy metals. For example, mean concentrations of lead and cadmium in Pomphorhynchus laevis were, respectively, 2700 and 400 times higher than in the muscle of the host (Leuciscus cephalus) and 11 000 and 27 000 times higher than the concentrations in the water (Sures et al 1994;. Metal bioconcentration by ®sh parasites is not restricted to adult acanthocephalans but has also been demonstrated, to a lesser extent, in intestinal cestodes (Riggs et al 1987;Sures et al 1997a) and can occur in marine as well as freshwater parasite species (Sures et al 1997a).…”
Section: Introductionmentioning
confidence: 99%
“…Tenora et al (2000a) reported that Pb, Cd and Cr concentrations in Philometra ovata were 106.11, 119.09 and 43.52 times higher than host. Lead and cadmium levels in Pomphorhynchus laevis Müller, 1776 were 2700 and 400 times higher than in the muscle of the host (Sures et al, 1994a;Sures & Taracshewski, 1995). Similar results were also reported for other fish species infected with acanthocephalans and nematodes (Sures et al, 1994b;Sures et al, 1997;Genç et al, 2008).…”
Section: Discussionmentioning
confidence: 90%
“…Futhermore, Philometra ovata (nematode) served as sensitive indicator species of heavy metal pollution in freshwater ecosystem [93]. Also, the Pomphorhynchus laevis (acanthocephalan) may serves as a very sensitive biological indicator for the presence of lead in aquatic ecosystem [2]. The endoparasite L. intestinalis (cestode) was found to be suitable to reflect the amount of heavy metals in sediments, providing more reliable information about the actual pollution of the reservoir [94].…”
Section: Biological Indicators For Heavy Metal Contaminationsmentioning
confidence: 99%
“…Extensive studies have been conducted on the use of marine fish parasites to assess the ecological conditions of marine ecosystems. Fish parasites have been explored as possible use in varieties of ways that could help scientists in solving certain issues such as issues on food chain structure [1], pollution [2][3][4][5][6][7][8][9][10], global climate change [11,12], anthropogenic impacts, environmental stresses and general ecosystem health [13], heavy metal pollution in the aquatic environment; b) The monogenean (Pseudorhabdosynochus), digenean (Didymodiclinus), nematodes (Spirophilometra, Philometra, and Raphidascaris), and acanthocephalan (Serrasentis) for anthropogenic impacts/environmental stresses/ pollution; and c) The anisakid nematode (Anisakis) for fish stock assessment. The acanthocephalans (Pomphorhynchus and Acanthocephalus) reported to have beneficial effect to their host by reducing heavy metal from their respective host fishes is also presented.…”
Section: Introductionmentioning
confidence: 99%